(3EOGQI GdYedjGJ GdeUQajIs - (3NGdO hgjH(B, (3GdQGhjs ((3YeGf(B:s (3OGQ GdefGgL ddfTQ hGdfhRjY(B,s, 2001)
(3GdLgGR GdeGdj hGdeUQaj aj GdCQOf(B- (3GdJWhQGJ GdEFJeGfjI hGdfbOjI(B- (3GdHfc GdeQcRj GdCQOfj hOhQg aj GdJfejI(B- (3JWhQ GdfXGe GdeGdj GdeUQaj aj GdGQOf(B- (3CfhGY GdeUGQa hhXGFagG(B- (3GdeaGgje GdMOjKI aj GSJNOeGJ GdCehGd aj GdeUGQa GdJLGQjI(B- (3eUGOQ Jehjd GdeUGQa GdJLGQjI(B- (3JfejI hEOGQI eUGOQ Jehjd GdeUQaj GdJLGQj(B- (3GdbhGFe GdeGdjI ddeUQa GdJLGQj(B- (3JMdjd GdbhGFe GdeGdjI(B- (3GdMhdGJ(B- (3GdcaGAGJ(B- (3GdEYJeGOGJ GdeSJfOjI(B- (3GdceHjGdGJ(B- (3GdHfhc GdESdGejI(B.s
Keywords: (3GdHfhc(B- (3GdCQOfs; (3GdeUGQas